Beyond species loss: the extinction of ecological interactions in a changing world. (28th November 2014) - Valiente‐Banuet, Alfonso; Aizen, Marcelo A.; Alcántara, Julio M.; Arroyo, Juan; Cocucci, Andrea; Galetti, Mauro; García, María B.; García, Daniel; Gómez, José M.; Jordano, Pedro; Medel, Rodrigo; Navarro, Luis; et al.
Summary: The effects of the present biodiversity crisis have been largely focused on the loss of species. However, a missed component of biodiversity loss that often accompanies or even precedes species disappearance is the extinction of ecological interactions. Here, we propose a novel model that (i) relates the diversity of both species and interactions along a gradient of environmental deterioration and (ii) explores how the rate of loss of ecological functions, and consequently of ecosystem services, can be accelerated or restrained depending on how the rate of species loss covaries with the rate of interactions loss. We find that the loss of species and interactions are decoupled, such that ecological interactions are often lost at a higher rate. This implies that the loss of ecological interactions may occur well before species disappearance, affecting species functionality and ecosystems services at a faster rate than species extinctions. We provide a number of empirical case studies illustrating these points. Our approach emphasizes the importance of focusing on species interactions as the major biodiversity component from which the 'health' of ecosystems depends. Abstract : Lay Summary